Macrozoobenthos Community Structure as an Indicator of Water Quality in the Intertidal Zone of Pariaman City, West Sumatra Province - Manalu, Govinda Hendra; Siregar, Yusni Ikhwan; Tanjung, Afrizal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Community structure refers to the arrangement and composition of species in a natural community and their abundance. Ecologists use various indices to assess community structure, including diversity index, evenness index, and dominance index. One helpful indicator for evaluating water quality is the presence and characteristics of macrozoobenthos, organisms living in the sediment of aquatic environments. The study focused on the community structure of macrozoobenthos as an indicator of water quality in the coastal waters of Pariaman City, West Sumatra. Conducted between February and March 2023, the research analyzed samples collected from the Marine Biology and Marine Chemistry Laboratories at Universitas Riau. Findings revealed the presence of 7 phylum, eight genera, and 16 macrozoobenthos species, with abundance ranging from 8.56 Ind/m2 to 18.44 ind/m2. The diversity index indicated moderate diversity, while the evenness index suggested an uneven distribution of individuals. No dominant species were found. Based on the analysis of macrozoobenthos community structure, water quality in Pariaman City's coastal waters was classified as good